Digital and analog learning media for improving fundamental movement skills in elementary school students: a prisma-guided systematic literature review - Wandi Geovani; Anton Komaini; Gusril Gusril; Umar Umar (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
Fundamental Movement Skills (FMS) are essential for children's physical development and lifelong participation in physical activity. However, many elementary school students still demonstrate low levels of locomotor, object-control, and stability skills. This systematic literature review examined the effectiveness of various learning media, including analog tools (e.g., flash cards and board games) and digital technologies (e.g., augmented reality, virtual reality, and mobile applications), in improving FMS among elementary school children. The review followed the PRISMA 2020 guidelines and used Scopus as the primary database. From 114 initially identified records, 10 studies met the final inclusion criteria and were analyzed in depth. Study quality was assessed using the FICO framework (Focus, Information, Context, Outcome). The findings indicate that game-based and flash-card learning media consistently improved locomotor skills, while augmented reality and mobile-based interventions produced equal or superior outcomes compared with conventional teaching methods. Adapted media, such as e-books and QR-code resources, also supported children with sensory or intellectual differences in developing FMS. Nevertheless, most studies employed small samples and single-group pretest–posttest designs, limiting the strength of causal inferences. Overall, learning media show considerable potential to enhance FMS development when systematically integrated into physical education programs. Future research should prioritize randomized controlled trials, longer intervention periods, and standardized reporting to strengthen the evidence base for educational practice and policy.